Creation and Transfer of Knowledge Institutions and Incentives - Barba Navaretti, Giorgio; Dasgupta, Partha; Mäler, Karl-Göran; Siniscalco, Domenico (Springer Berlin Heidelberg, 1998)
Is knowledge an economic good? Which are the characteristics of the institutions regulating the production and diffusion of knowledge? Cumulation of knowledge is a key determinant of economic growth, but only recently knowledge has moved to the core of economic analysis. Recent literature also gives profound insights into events like scientific progress, artistic and craft development which have been rarely addressed as socio-economic institutions, being the domain of sociologists and historians rather than economists. This volume adopts a multidisciplinary approach to bring knowledge in the focus of attention, as a key economic issue